(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Background: Reproductive health is a state of complete physical, mental and social well-being in all matters relating to the function, role and system of reproduction. Lack of adolescent knowledge about reproductive health can cause problems in their reproductive health. Problems that will arise if adolescents do not have sufficient knowledge about reproductive health are sexually transmitted diseases and sexually transmitted infections. Adolescent knowledge about health reproduction is still low with the result that 73.46% of male adolescents and 75.6% of female adolescents aged 15-19 years in Indonesia do not have sufficient knowledge about reproductive health. This lack of knowledge causes the incidence of stunting to increase, this is because adolescents, especially female adolescents, are less prepared when they are pregnant and adolescents should pay attention to nutrition during pregnancy. Many problems will arise due to ignoring reproductive health. Problems that arise due to lack of knowledge about reproductive health are KTD, abortion, early marriage and marriage, STIs or STDs and HIV/AIDS. According to data from PKBI (Indonesian Family Planning Association) Central Java in 2010, teenagers who had premarital sex were 863 people, 452 people got pregnant before marriage, 283 people had sexually transmitted infections, 337 people had masturbation, 244 people had abortions. This case has increased from 2009 where cases of teenagers who had premarital sex were 765 people, 367 people got pregnant before marriage, 275 people had sexually transmitted infections, 322 people had masturbation, 166 people had abortions (PILAR PKBI, 2010), Result and Conclusion : this causes teenagers to have early marriages which ultimately causes teenagers to be mentally or psychologically not ready to get pregnant so that teenagers’ knowledge in fulfilling nutrition during pregnancy and regarding the provision of a balanced menu for toddlers can affect the provision of food for toddlers. In fact, the nutritional status of toddlers is one of the indicators in health development in Indonesia and the incidence of stunting will decrease when toddler nutrition is optimally met.